Reaction norm analysis of fisheries-induced adaptive change and the case of the Northeast Arctic cod - Heino, Mikko; Dieckmann, Ulf; Godø, Olav Rune (ICES, 2002)
We present a probabilistic concept of reaction norms for age and size at maturation, and outline methods that can be used for their estimation in typical fisheries data. Such estimations are critical for calibrating size- and age-structured population models, for understanding phenotypic plasticity and life-history changes in variable environments, and for assessing genetic changes in the presence of phenotypic plasticity. We apply the method of reaction norm estimation to a set of measurements on Northeast Arctic cod collected between 1932 and 1998. This cod stock has shown a drastic reduction in age at maturation. In the 1930’s, age at maturation was typically around 10-11 years, whereas nowadays seven years is more usual. This change has been attributed both to fisheries-induced genetic selection for earlier maturation, and to a compensatory response caused by faster individual growth rate. However, previous analyses have been unable to disentangle these hypotheses. Our analysis, based on estimation of maturation reaction norms, shows that both increase in growth rate and change in age- and size-specific tendency to mature have contributed to the observed trend towards earlier maturation. The latter component probably represents a fisheries-induced adaptive genetic change.